Single beam Z-scan measurements of nonlinear refraction and nonlinear absorption coefficients in silver nano-fluid - Shahriari, Esmaeil; Mat Yunus, Wan Mahmood (Science Publications, 2010)
Problem statement: The nonlinear refractive index and nonlinear absorption are two important optical phenomena which are extensively used in optical switching, optical limiting and labeling. Approach: In the present research we had measured nonlinearity of Ag nano-fluid prepared using g-irradiation method. The measurement was carried out using a single beam z-scan technique. Under a CW laser beam excitation operated at 532 nm with the power output of 40 mW, a closed aperture setup was used for thermal-induced nonlinear refractive index and an open aperture setup was applied for measuring nonlinearity absorption. Results: We measured the nonlinear refraction coefficient and nonlinear absorption coefficients for silver nano-fluid at concentration 6.475×10-3 M,the values obtained were -6.173×10-8 cm2 W-1 and 7.994×10-3 cm W-1 respectively. Conclusion: The nonlinear refraction coefficient with the negative sign indicates the self-defocusing phenomenon. The experimental data from open aperture measurement showed that a two photon absorption phenomenon. These results showed that the Ag nano-fluid has significant values of nonlinear refractive index and nonlinear absorption, thus it could be good candidate for optical devices.